Peran Hukum Pranata Pembangunan dalam Pelestarian Rumah Adat Malige di Sulawesi Tenggara - Fayrooz Zahira Rizal Makkajareng; Lallo, St Fatmawati (Anoa : Jurnal Pengabdian Masyarakat Fakultas Teknik, 2025)
The Malige traditional house is a cultural heritage with high historical and architectural value for the people of Southeast Sulawesi, especially the Buton tribe. Preserving this traditional house is very important considering its function not only as a physical building but also as a cultural, spiritual, and social symbol for the local community. The urgency of this research is to understand the role of legal frameworks in supporting the preservation of the Malige traditional house to maintain the cultural values it embodies. The issues identified include insufficient socialization, inadequate coordination among institutions, and limited resources in implementing these regulations. The research employs a qualitative method with descriptive analysis techniques, relying on literature reviews and studies of relevant development regulations. The expected outcomes of this research are policy recommendations to strengthen specific regulations, enhance community participation, and ensure the effective and sustainable preservation of the Malige traditional house.